Astronomical forcing on loess deposition in the Junggar Basin since the late Pliocene - Zhixiang Wang; Tianfu Zhang; Alexis Licht; Mengmeng Cao; Rui Zhang (PANGAEA, 2023)
Herein, we present paleomagnetic, GR and Rb/Sr data over the past 3.5 Ma from the ZK01 core in the southern Junggar Basin, Northwestern China. We took 300 oriented samples along the core (ca. 1 sample every 1.5 m) for magnetostratigraphic dating. The corresponding boundaries of the Brunhes/Matuyama and Matuyama/Gauss transitions are at about 59 m and 315 m interval in the ZK01 borehole, respectively. To complete the lithological description of this core, we selected 17 samples between levels 100 and 425 m for grain size analysis. Our grain size shows an eolian deposit. Gamma ray (GR; ~5 cm sampling resolution) well log data and Rb/Sr ratios in the ZK01 core were used to carry out astronomical tuning. Our results show that GR data are dominated by 405 kyr cycles before ~2.8 Ma; ~100 kyr short eccentricity and obliquity cycles are significantly enhanced between 2.8 Ma and 1.4 Ma; the obliquity signal finally strengthens between 1.4 and ~0.55 Ma. By contrast, our Rb/Sr data show monotonic, dominant 405-kyr cycles with weak 100-kyr eccentricity, obliquity (41 kyr) and precession (20 kyr) cycles in the past 3.5 Ma. To complete the lithological description of the core, we selected 17 samples between levels 100 and 425 m for grain size analysis. We selected 2 samples for scanning electron microscope (SEM) analysis of quartz particles at 317 m and 415 m, in order to investigate potential marks for aeolian transport of the sediment. We took 300 oriented samples along the core (ca. 1 sample every 1.5 m) for magnetostratigraphic dating. A total of 1201 power samples were measured with an Innov-X Systems X-ray fluorescence spectrometer in geochemistry mode using beam 1 (50 kv) and beam 2 (10 kv) to acquire the abundance of rubidium (Rb) and strontium (Sr) at the Chinese University of Geosciences (Wuhan). The continuous GR data were measured using FD-3019 γ logging tool based on EJ/T 611-2005 gamma logging specification through pipes.